1999
DOI: 10.1038/emm.1999.27
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-dependent effects of oxidized LDL: proliferation or cell death

Abstract: Oxidized low-density lipoprotein (oxLDL) induces a wide range of cellular responses to produce atherosclerotic lesion, but key factors determining the response are not understood. In this study, purified LDL was oxidized with copper sulfate, and its physical properties and the related biological responses were investigated. The average hydrodynamic diameter of the lightly oxidized LDL was approximately 25 nm and its Rf value relative to nLDL on agarose gel was between 1.0 and 1.25. The diameter of the extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
3
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 44 publications
5
33
3
2
Order By: Relevance
“…Several factors may account for this apparent contradiction, but we believe the most important is that the pro-survival effect of ox-LDL is seen at concentrations between 10 and 75 g/ml, whereas at higher concentrations cytotoxicity predominates (19,54). Nearly all reports of ox-LDL-induced apoptosis or cytotoxicity involve ox-LDL concentrations in excess of 100 g/ml.…”
Section: Discussionmentioning
confidence: 71%
“…Several factors may account for this apparent contradiction, but we believe the most important is that the pro-survival effect of ox-LDL is seen at concentrations between 10 and 75 g/ml, whereas at higher concentrations cytotoxicity predominates (19,54). Nearly all reports of ox-LDL-induced apoptosis or cytotoxicity involve ox-LDL concentrations in excess of 100 g/ml.…”
Section: Discussionmentioning
confidence: 71%
“…Mouse RAW264.7 cells are a macrophagelike cell line and can be induced to form foam cells in the presence of oxLDL (Supplementary information, Figure S1) [24]. It could also be induced to form foam cells by berberine without the addition of oxLDL (Figure 2A).…”
Section: Berberine Promotes Foam Cell Formation By Inducing Sr-amentioning
confidence: 86%
“…The promotion of atherosclerosis resulted from berberine-induced in vivo foam cell formation. Using RAW264.7 cells, which can be induced by oxidized LDL (oxLDL) to form foam cells [24], we have identified that berberine induces the expression of scavenger receptor A (SR-A) through modulating the PI3-kinase signaling pathway. Specifically, by inactivating PPARγ, berberine inhibits PTEN expression and thus enhances PI3-kinase signaling.…”
Section: Introductionmentioning
confidence: 99%
“…OxLDL has a transient role in the mitogenic effect of macrophages, but finally causes cell death through the induction of apoptosis and necrosis. 31,32 Several factors such as ischemia, inflammatory cytokines, and the accumulation of toxic substances may also affect cell death in atherosclerotic plaques. 11 In this study, as for the relation of oxLDL to smooth muscle cell apoptosis, the apoptotic smooth muscle cell index increased with atherosclerotic development, and the apoptotic smooth muscle cells were detected mainly in the shoulder region and fibrous cap, where oxLDL-positive cells were predominant.…”
Section: Discussionmentioning
confidence: 99%